Planowanie i organizacja działań public relations w przedsiębiorstwach (w świetle badań ankietowych) - Daszkiewicz, Magdalena (Planning and Organizing Corporate Public Relations (On the Basis of the Questionnaire Research), 2006)
The article discusses problems of planning and organizing corporate public relations. The author made an attempt to analyze the situation in the field of public relations activities on the Polish market. The empirical illustration of the discussed problems comes from the results of the questionnaire research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 95-109